GUDA VARTI FOR POST-OPERATIVE PAIN MANAGEMENT- ROAD LESS TRAVELLED - Vilas Thakre Kalpita,; P Bhat Ramesh, (International Journal of Ayurveda and Pharma Research, 2021)
Acute pain is an unpleasant sensory, emotional and mental sensation (experience) associated with vegetative signs, psychological response and changes in behavior. Post-operative pain is one such example and adequate management becomes utmost necessary. In Shalya tantra practice, proctology is the field of excellence for many practitioners and post-operative pain is an acquaintance difficult to handle. Many practitioners still resort to using contemporary I.M OR I.V analgesics for pain management which have proven ADR’S due to lack of availability of Ayurvedic analgesics for management. Vartis (suppositories) was in vogue since pre-historic times and have been mentioned in almost all Ayurvedic texts for various disorders with suitable formulations and various modes of insertion, e.g.: Ratadi varti for Shoola. Ayurveda also has a wide-range of drugs mentioned for relieving pain which have not been used to the full potential. Hence Guda varti as a drug delivery system for pain management needs to be explored in Ayurveda Shalya tantra practice.